Educational resources in the module of statistics - Rigão, Maria Helena; Iop, Maria Cristina (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
This research aimed to promote and expand the presence of information and communication technologies in the educational dimension of Statistics teaching, favoring integration, interactivity and collaboration among those involved in the educational process and trainer UFSM. The subjects involved were: Introduction to Probability and Statistics and Applied Statistics Quality. As a result, it became clear that the use of ICT resources in educational activities proposed, promoted the autonomy and technological fluency of students, as well as collaboration and interaction between them. It was concluded that the integration between ICT and other resources, traditionally used in the discipline of Statistics, as success factor contributed to the training of students